Personalized Piperacillin Dosing for the Critically Ill: A Retrospective Analysis of Clinical Experience with Dosing Software and Therapeutic Drug Monitoring to Optimize Antimicrobial Dosing - Ute Chiriac; Daniel C. Richter; Otto R. Frey; Anka C. Röhr; Sophia Helbig; Judit Preisenberger; Stefan Hagel; Jason A. Roberts; Markus A. Weigand; Alexander Brinkmann (MDPI AG, 2021)
Optimization of antibiotic dosing is a treatment intervention that is likely to improve outcomes in severe infections. The aim of this retrospective study was to describe the therapeutic exposure of steady state piperacillin concentrations (cPIP) and clinical outcome in critically ill patients with sepsis or septic shock who received continuous infusion of piperacillin with dosing personalized through software-guided empiric dosing and therapeutic drug monitoring (TDM). Therapeutic drug exposure was defined as cPIP of 32-64 mg/L (2-4× the 'MIC breakpoint' of Pseudomonas aeruginosa). Of the 1544 patients screened, we included 179 patients (335 serum concentrations), of whom 89% achieved the minimum therapeutic exposure of >32 mg/L and 12% achieved potentially harmful cPIP > 96 mg/L within the first 48 h. Therapeutic exposure was achieved in 40% of the patients. Subsequent TDM-guided dose adjustments significantly enhanced therapeutic exposure to 65%, and significantly reduced cPIP > 96 mg/L to 5%. Mortality in patients with cPIP > 96 mg/L (13/21; 62%) (OR 5.257, 95% CI 1.867-14.802, p = 0.001) or 64-96 mg/L (30/76; 45%) (OR 2.696, 95% CI 1.301-5.586, p = 0.007) was significantly higher compared to patients with therapeutic exposure (17/72; 24%). Given the observed variability in critically ill patients, combining the application of dosing software and consecutive TDM increases therapeutic drug exposure of piperacillin in patients with sepsis and septic shock.